Seaweed extracts slightly reduce effects of root knot nematodes on tomato plants - Shah, F.A.; Butler, R.C.; Bulman, S.R.; Nelson, W.R.; Fletcher, J.D.; Scott, I.A.W. (New Zealand Plant Protection, 2010)
Root knot nematodes (Meloidogyne species) are economically important pathogens of a number of plants species worldwide A glasshouse pot experiment was carried out to compare the performance of an organic seaweed product (Kelpak) with that of the traditional nematicide fenamiphos (Nemacur) for the control of M fallax in tomato Root systems of seaweed and fenamiphostreated plants were less affected by M fallax than those in untreated controls although differences in root gall index for the treatments were not statistically significant (P031) Plant parameters were increased by the treatments but only for shoot height was the increase statistically significant (P005) Visual observation revealed that the roots systems of seaweedtreated plants were more dense and paler in colour than those from the untreated and fenamiphostreated plants which had dark brown roots The experiment has not found compelling evidence of high efficacy of seaweed extract against nematodes attacking tomato Effectiveness of these products warrants further study however including using different combinations of materials and timing of application aiming to determine if they are useful as part of integrated nematode management